Technological Architecture for Open Smart Cities - Kaschel-Carcamo, H; Palominos-Belmar, P; Martin-Quijada, R; Quiroga-Parraga, J (IEEE, 2021)
Rapid urban growth as a result of migration from rural to urban areas, reaching a urbanization rate of 68% by 2050, has put pressure on management, planning and development of cities, which has generated major problems such as pollution, urban inequality, bad mobility among other challenges. In recent years a new paradigm has emerged to face these challenges and it is the concept of smart cities and lately of Open Smart Cities One of the fundamental pillars to transform cities into smart cities is to have an enabling ICT infrastructure. In this paper, the state of the art of technological architecture to achieve Open Smart Cities is presented.